MULTIDISCIPLINARY CARE IN THE TREATMENT OF DIABETIC FOOT: A LITERATURE REVIEW: assistência multidisciplina no tratamento do pé diabético: revisão da literatura - MARIA VIANA,; João José da Silva Neto,; Adriele Florisa da Silva Anacleto,; Inara Larissa Ferreira Olegário,; Rafael da Silva Machado,; Dyego Anderson Alves de Farias, (Revista de Ciências da Saúde Nova Esperança, 2025)
Diabetic foot is a chronic lesion associated with diabetic neuropathy and peripheral arterial disease, characterized by affecting the lower limbs as a result of uncontrolled diabetes mellitus (DM), constituting one of the main causes of non-traumatic amputations worldwide. The management of this condition must be integrated and specialized, aiming at the functional rehabilitation of the affected limb. In this context, this study aimed to analyze the importance of multidisciplinary care in the treatment of diabetic foot, highlighting its benefits in preventing complications and in patient rehabilitation. This is an integrative literature review conducted in five databases: BDENF, LILACS, MEDLINE, IBECS, and PubMed/MEDLINE, through the Virtual Health Library (VHL). The descriptors “Foot ulcer” and “Multidisciplinary team” were used, combined with the Boolean operator “AND,” with a descriptive data analysis. Ten original articles were selected for the final sample, published between 2020 and 2025, in Portuguese, English, and Spanish. The results show that the interdisciplinary work of the multidisciplinary team is associated with significant clinical outcomes, including the reduction of major and minor amputation rates, shorter hospitalization time, accelerated healing process, and reduced hospital costs. The findings reinforce that integrated action among professionals from different health areas, such as nursing, vascular surgery, podiatry, nutrition, and physiotherapy, is essential not only for defining therapeutic treatment but also for developing educational actions directed at patients. It is concluded that multiprofessional practice is crucial for a safe and holistic approach to patients with diabetic foot, and treatment should be based on a collaborative model that integrates the clinical characteristics of the individual, with a preventive, educational, and rehabilitative focus.